2005
DOI: 10.3748/wjg.v11.i47.7430
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of DA-9601 on chronic reflux gastritis induced by sodium taurocholate in rats

Abstract: We suggest that DA-9601 is a promising agent for the treatment of chronic erosive and atrophic gastritis with an etiological factor of bile reflux. Increased mucosal prostaglandin E2 and reduced glutathione by DA-9601 treatment may be therapeutic mechanisms for chronic erosive and atrophic gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The chemical constituents of the essential oil have also been investigated [15], and the antimicrobial assays of the essential oil components revealed the antibacterial and antifungal activity of the monoterpene alcohol fraction and the main constituents 1,8-cineole and selin-11-en-4α-ol [16]. Earlier studies have demonstrated that A. asiatica contains a high amount of eupatilin (10), a flavone which exhibits cytotoxic activity through the induction of cell cycle arrest and the differentiation of gastric carcinoma and endometrial cancer cells [17]. Further, eupatilin has been shown to possess an antimetastatic effect against a human gastric cancer cell line [18].…”
mentioning
confidence: 99%
“…The chemical constituents of the essential oil have also been investigated [15], and the antimicrobial assays of the essential oil components revealed the antibacterial and antifungal activity of the monoterpene alcohol fraction and the main constituents 1,8-cineole and selin-11-en-4α-ol [16]. Earlier studies have demonstrated that A. asiatica contains a high amount of eupatilin (10), a flavone which exhibits cytotoxic activity through the induction of cell cycle arrest and the differentiation of gastric carcinoma and endometrial cancer cells [17]. Further, eupatilin has been shown to possess an antimetastatic effect against a human gastric cancer cell line [18].…”
mentioning
confidence: 99%
“…23 Even the susceptibility of patients using NSAIDs to gastric mucosal damage by alcohol was also shown to be reduced by DA-9601. 22 The present study demonstrated that the production and secretion of ghrelin increased more in DA-9601-pretreated rats subsequently exposed to alcohol or indomethacin than in the placebo-pretreated rats suggesting that increased production of ghrelin may be responsible for the gastro-protective effect of DA-9601. Ghrelin has beneficial effects on various inflammatory conditions.…”
Section: Discussionmentioning
confidence: 61%
“…20,21 DA-9601 is reported to inhibit xanthine oxidase and thereby suppress oxidative stress and to prevent acute gastrohemorrhagic injury by ethanol. 6 It has been used to treat erosive gastritis and atrophic gastritis, 22 and its efficacy against erosive gastritis was reported to be higher than that of cetrexate. 23 Even the susceptibility of patients using NSAIDs to gastric mucosal damage by alcohol was also shown to be reduced by DA-9601.…”
Section: Discussionmentioning
confidence: 99%
“…Although we presented the detailed data about DA-9601 treatment, ethanol extracts of Artemisia asiatica [ 11 ], among several gastroprotectants [ 8 – 10 ], which is one of gastroprotectants prescribed popularly for the treatment of gastritis and peptic ulcer disease in Korea, possessing actions like anti-inflammatory, cytoprotective, restorative, and antioxidative actions [ 11 , 21 24 ], we repeated the same experiment with other gastroprotectants available in clinic like rebamipide and ecabet sodium, and found that the overall rates of resistance to ulcer recurrence experiment according to gastric cytoprotectants were 2/12 (16.7%) with DA-9601, 3/12 (25.0%) with rebamipide, and 3/11 (27.2%) with ecabet sodium, respectively. Hence, we can’t ignore the principal role of acid suppressant in the treatment of gastric ulcer, our suggestions from the current experiment were that in order to achieve rapid symptom relief, accelerated healing, and resistance to ulcer relapse, the combined use of acid suppressant and gastroprotectant should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Omeprazole was administered as acid suppressant and DA-9601 was used as gastric cytoprotectant. DA-9601 used in the current study was demonstrated to possess cytoprotective actions in various experimental models, including ethanol-induced gastric mucosal damage, reflux esophagitis, and trinitrobenzosulfonic acid (TNBS)-induced colitis, of which mechanisms were stimulation of mucus, PG, glutathione and antioxidative actions [ 11 , 21 24 ].…”
Section: Introductionmentioning
confidence: 99%